A decision support system for control mechanism of inventory in a dynamic supply chain system considering supply-price trade-off using control theory. (1st January 2013) - Kumar, Anup; Mukherjee, Kampan; Kumar, Narendra
This paper presents a conceptual insight to model a dynamic supply chain system with discrete input and output. The entire supply chain can be modelled by combining the transfer function into a closed-loop system. The transfer function of each entity in the supply chain can be obtained by using the control theory tools. The model can be approximated as a linear discrete system with various operating constants, like lead time, price, order policy and supply. The stability (sustainability) of the system can be analysed using the closed-loop transfer function. Different control strategy can be designed using frequency domain analysis. Bullwhip effect is controlled in an effective manner using different control strategy. This model will be helpful in developing an automated smart supply chain system, incorporating the effect of price change and other wide sense stationary random variables in the supply chain system. The objective of this work is to develop a model that can be used for decision support for control of different parameters including price, subject to different control strategies.